Analysis of the Pseudo-Thinking Process of Field-Dependent 8th-Grade Students at SMP Negeri 2 Palu in Solving Pythagorean Theorem Problems - wianita selviani; Mubarik Mubarik; Pathuddin Pathuddin; Alfisyahra Alfisyahra (Universitas Islam Sultan Agung, 2026)
The occurrence of pseudo-thinking processes in mathematics learning remains prevalent, as many students solve problems by relying on memorized procedures rather than understanding the underlying concepts. While previous research has largely focused on error analysis or general problem-solving abilities, studies specifically examining pseudo-thinking processes among field-dependent students when solving Pythagorean theorem problems remain limited. This study aims to analyze the pseudo-thinking processes of eighth-grade students at SMP Negeri 2 Palu specifically those with a field-dependent cognitive style while solving Pythagorean theorem problems, by examining the relationship between cognitive style characteristics and pseudo-thinking processes. A descriptive qualitative approach was employed. Data were collected from a single student, purposively selected to represent the field-dependent cognitive style, using the Group Embedded Figures Test (GEFT), a Pythagorean theorem problem-solving test, and semi-structured interviews. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing/verification. The results indicate that the field-dependent student exhibited